The cancer incidence and mortality among children and adolescents during the period of 2010‐2014 in Henan Province, China. (18th January 2019) - Chen, Qiong; Guo, Zhen; Liu, Shuzheng; Quan, Peiliang; Cao, Xiaoqin; Guo, Lanwei; Zhang, Shaokai; Sun, Xibin
Abstract: Objective: The cancer etiology in children and adolescents is largely different with that in adults, and the description in epidemiology still remains deficiency. Therefore, we described the cancer incidence and related epidemiological features in children and adolescents to provide clues for etiological studies. Methods: Cancer incidence stratified by age, gender, and areas was calculated using data extracted from population‐based cancer registries in Henan Province, China. All cancer among children aged 0‐19 years were reclassified according to category criteria of the International Classification of Childhood Cancer, 3rd Edition (ICCC‐3). Age‐standardized rate (WSR) was calculated using Segi's world standardized population by the direct method, and it was expressed per million person‐years. Results: The crude cancer incidence and mortality were 87.56 and 36.32 per million person‐years among children aged 0‐19 years, and the WSRs slightly changed compared with crude incidence and mortality, and they were 87.36 and 35.46 per million person‐years. Leukemia and central nervous system neoplasms (CNS) were the most common cancer categories both in children aged 0‐14 years and in adolescents aged 15‐19 years in regardless of gender and areas. Tiny difference of incidence and mortality existed in different age groups across 0‐14 years; however, they were higher in adolescents aged 15‐19 years than that in children aged 0‐14 years. Among children aged 0‐19 years, the cancer incidence and mortality were predominant in boys, and the sex ratio was 1.19; however, it was varied by diagnostic categories. Conclusion: This is the first study that described the cancer incidence and mortality among children aged 0‐19 in Henan Province, and it would help researchers to understand the burden and epidemiological characteristics of childhood cancer, and hence suggested clues for the etiological studies. Abstract : The description in epidemiology of childhood cancer still remains deficiency, and our study suggested that the crude cancer incidence and mortality were 87.56 and 36.32 per million person‐years among children aged 0‐19 years in Henan, China. Leukemia and central nervous system neoplasms (CNS) were the most common cancer categories both in children aged 0‐14 years and in adolescents in regardless of gender and areas.